Perspectives on Genetic Research: Results From a Survey of Navajo Community Members - Claw, Katrina G.; Dundas, Nicolas; Parrish, Michael S.; Begay, Rene L.; Teller, Travis L.; Garrison, Nanibaa’ A.; Sage, Franklin (Frontiers in Genetics, 2021)
The Navajo Nation placed a moratorium on genetic research studies in 2002, in part due to concerns about historical distrust, exploitation, limited expertise and resources, and the lack of a genetics policy. Navajo tribal leaders, scientists, and policy experts are exploring the possibility of lifting the moratorium, developing a genetic research policy, and discussing its potential health implications. This study aimed to identify the key concerns, needs, and desires of Navajo people regarding genetic research. We conducted a survey of Navajo individuals to assess knowledge of the moratorium and research, gauge interest in genetic research, and quantify appropriate genetic research topics to understand broad views and concerns. We performed descriptive statistics and tested associations between relevant categorical variables using Chi-square tests. We hypothesized that individuals with more knowledge about the moratorium and health research increased the likelihood of supporting and participating in genetic research. A total of 690 surveys from Navajo respondents were analyzed. Of these, 63% of respondents reported being unaware of the Navajo Nation’s moratorium on genetic research. There were positive associations between those who knew about the moratorium and willingness to donate biospecimens for research under certain conditions, such as community involvement, review and approval by community leaders, research on diseases affecting the community, and support for lifting the moratorium (p-values<0.001). We found no significant differences between age, gender, religious/spiritual beliefs, or agency affiliation with knowledge levels of genetics and related topics, participation in relation to beliefs, and donation of biospecimens. Interestingly, respondents who resided off the Navajo Nation were positively associated with having knowledge of the moratorium, having heard of discussions of genetics on the Navajo Nation, and the lawsuit filed by the Havasupai Tribe. Most respondents agreed that it was very important to develop a policy that incorporates cultural knowledge (56%), is beneficial (56%), and has data sharing protections (59%) before allowing genetic research on the Navajo Nation. Overall, a large proportion of respondents (46%) were unsure about lifting the moratorium and instead wanted more genetics education to assess its potential implications. The study results can inform the direction of future guidelines and policies.